Recognizing the Need to Seek Help: Signals that Trigger Academic Help-Seeking among University Students - Valenzuela, Jorge (2025)
Objective. The present study examines the signals that students consider clear indicators for seeking help at university, as well as the variables associated with those students who realize they need assistance only after failing a course. Method. In the study, 753 students from different fields and universities responded to a questionnaire on motivational variables related to seeking academic help. Results. The results indicate that poor grades are the most important signal for seeking help. On the other hand, it was found that 10% of the sample who needed to fail the course to realize they required help were characterized by greater shame, less social and academic integration, and less vocational strength. They also had a lower appreciation of academic support.